Analisa Perbandingan Algoritma Huffman Codes Dan Algoritma Boldi Vigna Codes Dalam Mengkompresi Data Teks - Harefa, Erni Krisniat (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2024)
Data compression (data utilization) is a technique to reduce the amount of data size (compression result) of the original data. To solve this problem, it is recommended to compress text files with a suitable algorithm to get optimal results. The analysis is done by comparing the working process of Huffman algorithm and Boldi Vigna algorithm. To compress text files these two algorithms are measured by Compression Ratio, Birate, Space Caving, and Time Compression. the file to be compressed is a text file in TXT format. Text file compression minimizes the storage of a collection of bits in a text file resulting in a smaller size. In the comparison of the two Huffman algorithms with Boldi Vigna, both have a type of lossless compression algorithm, which is a type of compression that can be decompressed and the results obtained from the comparison of the two algorithms, that the Huffman algorithm is superior to Boldi Vigna.